Pelatihan Membuat Video Pembelajaran Berbasis Bandicam Bagi Mahasiswa UNDIKMA - M. Fuaddunazmi; Baiq Rina Amalia Safitri (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
The purpose of this service is to help trainees be able to make learning media in the form of videos. The training method used is the lecture method and uses the Direct Instruction learning model. As for the material presented, there are two: 1. Install the Bandicam application to make learning videos, and 2. Setting the Bandicam application as desired. The training is carried outat UNDIKMA to be precise for students who will soon complete their studies or final semester students or students who are currently pursuing their thesis or prospective educators. The results of the training conducted were that participants were able to install the Bandicam application themselves and students were able to set up the Bandicam application according to what the participants wanted. More importantly, the participants are able to make their own learning videos.